White sponge nevus: a case report and literature review - HONG Pengyu; GAO Jiaxiong; WANG Dianri; TANG Zhangui (口腔疾病防治, 2019)
Objective To explore the etiology, clinical manifestation, diagnosis and treatment of white spongy spot nevus, so as to provide reference for clinical diagnosis and treatment. Methods The clinical data and related literature of a case of white cavernous nevus in oral cavity were retrospectively analyzed. Results White spongy nevus is a rare autosomal dominant hereditary disease with a family history. The mutations of keratin gene K4 and K13 in patients with white spongy nevus are considered to be the main causes. The disease usually starts in children and adolescents and tends to be stable in adulthood. It is characterized by extensive white water⁃wave folds on the mucosa, soft texture, and affects the bilateral buccal mucosa. Pathological examination usually shows excessive keratosis of epithelial cells, ede⁃ ma and vacuolation in spinous cells, while basal cells are generally normal. In clinic, it should be differentiated from oral leukoplakia, oral lichen planus and oral candidiasis. At present, there is no specific treatment method. Retinoic acid is of⁃ ten applied locally and gargle is used to keep oral hygiene and cleanliness. Patients can not be treated without conscious symptoms. The prognosis of the disease is good and there is no tendency of malignancy. Conclusion White spongy ne⁃ vus is very rare and easily missed by clinicians. Diagnosis mainly depends on medical history, clinical manifestations and pathological examination. Future research directions should be devoted to finding more effective treatment.